2012
DOI: 10.1177/0888406412444762
|View full text |Cite
|
Sign up to set email alerts
|

The Supply

Abstract: As the field of special education (SE) examines issues related to supply and demand of SE teachers and faculty, an investigation of students currently enrolled in doctoral programs and doctoral graduates is an important perspective to consider. The results of two components of the Special Education Faculty Needs Assessment (SEFNA), focused on the aforementioned two populations, are described. Students enrolled in SE doctoral programs during the spring of 2009 (n = 1,263) and graduates of SE doctoral programs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similar to PreK-12 schools, EPPs grapple with balancing the delivery of impactful learning experiences and accountability expectations for undergraduate and graduate students. The pressure placed on EPPs that train special educators is even greater due to pervasive shortages of special education teacher educators (Robb, Smith & Montrosse, 2012;West & Hardman, 2012) and the demand of fully qualified special educators in PreK-12 schools (Tyler, Montrosse & Smith, 2012). To assist special education EPPs with ensuring they develop and implement high-quality programs, the Council for Exceptional Children (CEC, 2015) released the following set of six preparation standards:…”
Section: Overview Of Special Education Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to PreK-12 schools, EPPs grapple with balancing the delivery of impactful learning experiences and accountability expectations for undergraduate and graduate students. The pressure placed on EPPs that train special educators is even greater due to pervasive shortages of special education teacher educators (Robb, Smith & Montrosse, 2012;West & Hardman, 2012) and the demand of fully qualified special educators in PreK-12 schools (Tyler, Montrosse & Smith, 2012). To assist special education EPPs with ensuring they develop and implement high-quality programs, the Council for Exceptional Children (CEC, 2015) released the following set of six preparation standards:…”
Section: Overview Of Special Education Teacher Educationmentioning
confidence: 99%
“…Research has shown that PreK-12 special educators contend with increased assessment responsibilities and educational decision making for students with disabilities (Dukes et al, 2014;Smith et al, 2010;Tyler et al, 2012). Significant growth in the emerging number of multilingual students in U.S. schools requires that special educators and evaluators have the skills necessary to minimize bias, distinguish cultural and linguistic difference from disability, and implement needed services to students with disabilities (Chen & Lindo, 2018).…”
Section: Overview Of Special Education Teacher Educationmentioning
confidence: 99%
“…These funding opportunities may make the ultimate difference in your success, as many believe that “academic integration,” or becoming fully assimilated within the university, is the single most important factor in predicting those who complete their programs versus those who do not (Lovitts, 2001). Moreover, individuals who take advantage of some sort of assistantship (such as in teaching or research) or an available fellowship to support their doctoral program are 1.6 times as likely to become a university faculty member (Tyler, Mostrosse, & Smith, 2012). For this reason, taking advantage of opportunities that will allow you to be a full-time student may be invaluable.…”
Section: Step 6: Research Funding Possibilitiesmentioning
confidence: 99%